The essential role of AMPA receptor GluR2 subunit RNA editing in the normal and diseased brain - Wright, Amanda L.; Vissel, Bryce (Frontiers in Molecular Neuroscience, 2012)
AMPA receptors are comprised of different combinations of GluR1-GluR4 (also known as GluA1-GluA4 and GluR-A to GluR-D) subunits. The GluR2 subunit is subject to Q/R site RNA editing by the ADAR2 enzyme, which converts a codon for glutamine (Q), present in the GluR2 gene, to a codon for arginine (R) found in the mRNA. AMPA receptors are calcium (Ca2+)-permeable if they contain the unedited GluR2(Q) subunit or if they lack the GluR2 subunit. While most AMPA receptors in the brain contain the edited GluR2(R) subunit and are therefore Ca2+-impermeable, recent evidence suggests that Ca2+-permeable GluR2-lacking AMPA receptors are important in synaptic plasticity and learning. However, the presence of Ca2+-permeable AMPA receptors containing unedited GluR2 leads to excitotoxic cell loss. Recent studies have indicated that RNA editing of GluR2 is deregulated in diseases, such as amyotrophic lateral sclerosis (ALS), as well in acute neurodegenerative conditions, such as ischemia. More recently, studies have investigated the regulation of RNA editing and possible causes for its deregulation during disease. In this review, we will explore the role of GluR2 RNA editing in the healthy and diseased brain and outline new insights into the mechanisms that control this process.